2008
DOI: 10.1021/je700753g
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Phase Equilibrium in the Aqueous Ternary System (KCl−CaCl2−H2O) at (288.15 and 308.15) K

Abstract: The solubility and the physicochemical properties (density and refractive index) in the liquid–solid metastable system (KCl−CaCl2−H2O) at (288.15 and 308.15) K were determined using the isothermal evaporation method. Based on the experimental data, the metastable phase diagrams and the diagrams of physicochemical properties vs composition in the system at (288.15 and 308.15) K were plotted. In the metastable phase diagrams of the ternary system at (288.15 and 308.15) K, there are in all one invariant point, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Maybe, it can be explained by different conditions, such as the precision of apparatus. Although the density value of KCl-H 2 O is 1.2364 g Á cm À3 at T = 308.15 K in reference [34], it is 1.2020 g Á cm À3 at T = 323.15 K in reference [24]. Except these literature data, we can see that our density value of KCl-H 2 O at T = 313.15 K keep consistent with the tendency comparing with other data.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Maybe, it can be explained by different conditions, such as the precision of apparatus. Although the density value of KCl-H 2 O is 1.2364 g Á cm À3 at T = 308.15 K in reference [34], it is 1.2020 g Á cm À3 at T = 323.15 K in reference [24]. Except these literature data, we can see that our density value of KCl-H 2 O at T = 313.15 K keep consistent with the tendency comparing with other data.…”
Section: Resultssupporting
confidence: 85%
“…But several data cannot keep consistent with the tendency, especially the density value of KCl-H 2 O at T = 308.15 K in Ref. [34] and refractive index data of K 2 SO 4 -H 2 O at T = 318.15 K in reference [33]. Maybe, it can be explained by different conditions, such as the precision of apparatus.…”
Section: Resultsmentioning
confidence: 93%
“…We do not want to burden the present paper with a complete list of references for 'metastable phase equilibria'. The typical experimental set-up used in most of the studies is, for example, found in references [1][2][3][4]. The authors call their experimental technique the 'isothermal evaporation method'.…”
Section: Introductionmentioning
confidence: 99%
“…The relative humidity of the air is usually quite low (typically, 20-35% RH) resulting in evaporation from the salt solution. The authors attempt to mimic the evaporation rates of particular salt lakes by adjusting both the flow velocity and the relative humidity in the chamber [1][2][3][4]. Solutions are not mixed during evaporation either by agitation or by stirring.…”
Section: Introductionmentioning
confidence: 99%
“…Although metastable equilibria of several systems have been reported, such as the sea water system (Na-K-Mg-Cl-SO 4 [6][7][8][9], those of the titled systems (NaCl-MgCl 2 -H 2 O) and (KCl-MgCl 2 -H 2 O) at 308.15 K have not been reported in the literature in terms of describing their metastable behavior. According to statistical meteorologic analyses in the most recent 20 years, the climate conditions in salt lake regions of the Qaidam Basin are generally windy, arid, with little rainfall and a great evaporating capacity.…”
Section: Introductionmentioning
confidence: 99%